Role of noradrenergic transmission within the ventral bed nucleus of the stria terminalis in nicotine withdrawal‐induced aversive behavior - Saya Arakaki; Masabumi Minami (Wiley, 2022)
Abstract Aim Cessation of smoking induces nicotine withdrawal symptoms such as anxiety, depression, and dysphoria, which could lead to smoking relapse. In the present study, we examined the role of noradrenergic transmission within the ventral bed nucleus of the stria terminalis (vBNST) on nicotine withdrawal‐induced aversive behavior. Methods Nicotine dependence in rats was established by subcutaneous implantation with a nicotine‐filled osmotic minipump on day 1. Nicotine withdrawal was precipitated by administration of the nicotine receptor antagonist, mecamylamine (3.0 mg/kg, s.c.), on day 15. Nicotine withdrawal‐induced intra‐vBNST noradrenaline release and aversive behavior were examined by in vivo microdialysis and a conditioned place aversion (CPA) test, respectively. Results Intra‐vBNST noradrenaline release was significantly increased during nicotine withdrawal. Nicotine withdrawal induced aversive behavior, which was attenuated by intra‐vBNST injection of the β‐adrenoceptor antagonist, timolol. Conclusions These results suggest that enhanced noradrenergic transmission via β‐adrenoceptors in the vBNST plays a crucial role in nicotine withdrawal‐induced aversive behavior.